Fuzzy System Identification Using Gaussian Mixture Models - Gan, Ming Tao (2007)
The thesis is structured into 4 major studies, each presented under a separate chapter.Chapter 1 - A theoretical bridge associating a Gaussian Mixture Model (GMM) to an additive fuzzy system is uncovered. Chapter 3 - Invoke the Jacobi vs Gauss_seidel analogy in an attempt to speed up the rate of EM convergence. Chapter 4 - The theses proposes an adaptation of the EM that minimizes the average predicted error, in conjunction with maximizing likelihood.